2009
DOI: 10.1515/dema-2013-0184
|View full text |Cite
|
Sign up to set email alerts
|

Free exponential families as kernel families

Abstract: Abstract. Free exponential families have been previously introduced as a special case of the q-exponential family. We show that free exponential families arise also from the approach analogous to the definition of exponential families by using the Cauchy-Stieltjes kernel 1/(1 − θx) instead of the exponential kernel exp(θx). We use this approach to re-derive some known results and to study further similarities with exponential families and reproductive exponential models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Barndorff-Nielsen and Thorbjørnsen (2006, p. 101). In particular, Bryc (2008) has developed the idea of free exponential families with quadratic variance functions.…”
Section: Discussionmentioning
confidence: 99%
“…Barndorff-Nielsen and Thorbjørnsen (2006, p. 101). In particular, Bryc (2008) has developed the idea of free exponential families with quadratic variance functions.…”
Section: Discussionmentioning
confidence: 99%
“…As pointed out in the introduction, reference [1] describe the class of quadratic CSK families; that is the class of CSK families such that the corresponding variance function is a polynomial function in the mean of degree at most 2. Up to affine transformation and powers of free convolution, this class consists of, the Wigner's semi-circle (free gaussian), the Marchenko Pastur (free Poisson), the free Pascal (free negative binomial), the free Gamma, the free analog of hyperbolic type law and the free binomial families.…”
Section: Characterizations Of the Quadratic Csk Familiesmentioning
confidence: 99%
“…In particular they have studied the case when q = 0 which is related to free probability theory by using the Cauchy-Stieltjes kernel 1/(1 − θx) instead of the exponential kernel exp(θx). In [1], Bryc continue the study of Cauchy-Stieltjes Kernel (CSK) families for compactly supported probability measures ν. He has shown that such families can be parameterized by the mean and under this parametrization, the family (and measure ν) is uniquely determined by the variance function V (m) and the mean m 0 of ν.…”
Section: Introductionmentioning
confidence: 99%
“…It follows from (15) by approximation that the vector on the right hand side of (17) belongs to X (n+1) . Furthermore,…”
Section: Proofsmentioning
confidence: 99%